Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Translators: _:n32037
Keywords: Crise; Famille; Femmes

Praticiennes et patientes. Les femmes et la santé dans l'historiographie québécoise - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1999)
issued: 1999-22-00
Keywords: Femmes; Médecine

Les cours d'instruction civique de la Fédération Nationale Saint-Jean-Baptiste. Une voie d'accès à la citoyenneté politique pour les femmes du Québec - Cohen, Yolande; Maillé, Chantal (Recherches féministes, 1999)
Number: 2
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

De Jeanne D'Arc à Madeleine de Verchères: la femme guerrière dans la société d'Ancien Régime - Gervais, Diane; Lusignan, Serge (Revue d'histoire de l'Amérique française, 1999)
issued: 1999-23-00
Keywords: Combat; Femmes; Forts

Writing Bodies: Modern Dance, Gender, and Jewish Identity in New York and Montreal, 1930 to 1960 - Hardt, Yvonne (Université Concordia, 1999)
Keywords: Danse; Juifs

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
issued: 1999-24-00
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

De la clandestinité à l'affirmation: pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)

Femmes et organisations environnementales, l'activisme au féminin: étude de cas - Laloux, Aurélie (Université du Québec à Montréal, 1999)
Keywords: Femmes; Groupes populaires

La structure spatiale des déplacements pendulaires des femmes et des hommes dans la région de Montréal - Lemelin, André; Gatignol, Agnès (Cahiers de géographie du Québec, 1999)
Number: 119

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

Barbe de Boullougne ou l’ascension d’une femme dans la Nouvelle-France du XVIIe siècle - Vachon, Louise (Université de Montréal, 1999)
Keywords: Confrérie de la Sainte-Famille; Confréries

L'aventure sexuelle clandestine: le cas du mont Royal - Allen, Luther A. (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Mont-Royal (parc); Parcs

Le projet Gilford: mémoires vives d'une pratique artistique et politique - Boisvert, Suzanne; Boutet, Danielle (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)

Voix et images de lesbiennes: la formation d'un réseau de médias - Bourque, Dominique (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Femmes

Re-Working Respectability: the Feminisation of Clerical Work and the Politics of Public Virtue in Early Twentieth-Century Montreal - Boyer, Kate (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Travail

La conquête d'un espace public: les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Alcool

Influence du processus d'insertion sur l'identité des femmes libanaises nouvellement arrivées à Montréal - Cossette, Maryse (Université du Québec à Montréal, 1998)
Keywords: Femmes; Libanais

Sortir de l'ombre: histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank W. (VLB, 1998)

Les lesbian pulps: un instrument de conscientisation - Fortier, Muriel (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Femmes

Le renforcement des normes sur la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children, 1882-1920 - Hébert, Fernand (Bulletin d'histoire politique, 1998)
issued: 1998-24-00
Keywords: Enfants; Famille; Femmes

Des lieux d'appartenance: les bars gais des années 1950 - Higgins, Ross (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Alcool

Genèse d'une communauté lesbienne: un récit des années 1970 - Hildebran, Andrea (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Anglophones; Femmes; Francophones

Gender, Race, and Power: the Chinese in Canada, 1920-1950 - Huang, Belinda (Université McGill, 1998)
Keywords: Chinois

La question lesbienne dans le féminisme montréalais: un chassé-croisé - Lamoureux, Diane (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Femmes; Féminisme

L'impossible réciprocité des rapports politiques et idéologiques entre le nationalisme radical et le féminisme radical au Québec 1961-1972 - Lanthier, Stéphanie (Université de Sherbrooke, 1998)
Keywords: Féminisme; Idéologies; Nationalisme

Deux solitudes: les organismes sida et la communauté gaie - Lavoie, René (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)

Les Québécoises et les débuts de l’État providence - Lévesque, Andrée (Itinera. Supplément de la Revue suisse d'histoire, 1998)
Number: 20
Keywords: Femmes

Painting Friends: The Beaver Hall Woman Painters - Meadowcroft, Barbara (Véhicule Press, 1998)
Keywords: Clubs; Femmes; Peinture

Qui t’a débauchée? Female Adolescent Sexuality and the Juvenile Delinquents’ Court in early Twentieth-Century Montreal - Myers, Tamara (Family Matters: Papers in Post-Confederation Canadian Family History, 1998)
Keywords: Délinquance; Enfants; Femmes; Tribunaux

Libération homosexuelle ou révolution socialiste? L'expérience du GHAP - Noël, Roger (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Groupes populaires

Manliness, Goodness, and God: Poverty, Gender, and Social Reform in English-Speaking Montreal, 1890-1929 - Perry, Ann Kirsten (Université Queen's, 1998)
Keywords: Anglophones; Pauvreté; Réformistes

Le Village gai de Montréal: entre le ghetto et l'espace identitaire - Remiggi, Frank W. (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)

Traces militantes éphémères: l'ADGQ et Le Berdache - Sivry, Jean-Michel (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Groupes populaires

Les femmes du Refus global - Smart, Patricia (1998)
Keywords: Automatistes; Femmes; Féminisme

Nationalisme et politiques des mouvements sociaux: les droits des gais et lesbiennes et l’incidence de la charte canadienne au Québec - Smith, Miriam (Politique et sociétés, 1998)
Number: 3
Keywords: Nationalisme

Itinéraire d'un courant politique: le lesbianisme radical au Québec - Turcotte, Louise (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Femmes

Des Adonis en quête d'immortalité : la photographie homoérotique - Waugh, Thomas (Sortir de l’ombre. Histoires des communautés lesbienne et gaie de Montréal, 1998)
Keywords: Photographie

EDWARDS, ANNA HARRIETTE - Yorke, Lois K. (Dictionnaire biographique du Canada, 1998)

Les scénarios sexuels des jeunes adultes latino-américains de Montréal l'impact de l'acculturation et du genre - Arroyo, Javiera (Université du Québec à Montréal, 1997)
Keywords: Latino-Américains

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

De la répression à la tolérance: l’homosexualité - Chamberland, Line (Cap-aux-Diamants, 1997)
issued: 1997-21-00

'Ruffled' Mistresses and 'Discontented' Maids: Respectability and the Case of Domestic Service, 1880-1914 - Fahrni, Magda (Labour / Le travail, 1997)
issued: 1997-21-00
Keywords: Domestiques; Femmes

Une organisation maternaliste au Québec, la Fédération nationale Saint-Jean-Baptiste (1900-1940) - Hébert, Karine (Université de Montréal, 1997)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

A Sense of Belonging: Pre-Liberation Space, Symbolics, and Leadership in Gay Montreal - Higgins, Ross (Université McGill, 1997)

Militantisme lesbien à Montréal, 1970-1980 - Hildebran, Andréa (Université du Québec à Montréal, 1997)
Keywords: Femmes

Housing the Grey Nuns: Power, Religion, and Women's in fin-de-siècle Montréal - Martin, Tania (Exploring Everyday Landscapes: Perspective in Vernacular Architecture, VII, 1997)
Keywords: Communautés religieuses; Couvents; Soeurs Grises

Étude exploratoire sur l'adaptation socio-sexuelle des immigrants latino-américains gais à Montréal - Pérez Luis, Javier Éric (Université du Québec à Montréal, 1997)
Keywords: Latino-Américains

To Indulge their Carnal Appetites: Prostitution in Early Nineteenth-Century Montreal, 1810-1842 - Poutanen, Mary Anne (Université de Montréal, 1997)
Keywords: Police; Prostitution; Tribunaux

Domesticating Parks and Mastering Playgrounds: Sexuality, Power and Place in Montreal, 1870-1930 - Schmidt, Sarah (Université McGill, 1997)
Keywords: Délinquance; Mont-Royal (parc); Parcs; Places publiques

'Archi-ettes' in Training: The Admission of Women to McGill's School of Architecture - Adams, Annmarie (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Femmes; Université McGill

Les rapports médecins-infirmières et l'implication de la Métropolitaine dans la lutte contre la mortalité infantile, 1909-53 - Baillargeon, Denyse (Canadian Historical Review, 1996)
Number: 1
Keywords: Assurance; Enfants; Infirmières; La Métropolitaine; Mortalité; Médecine

Menstruation Goes Public: Aspects of Women's Menstrual Experience in Montreal, 1920-1975 - Armeni, Elizabeth (Université McGill, 1996)
Keywords: Femmes

Fréquenter les Gouttes de lait: l'expérience des mères montréalaises, 1910-1965 - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1996)
Number: 1
Keywords: Enfants; Femmes; Goutte de lait; Mortalité

Table ronde. L'histoire des femmes: 25 ans de recherche et d'enseignement - Baillargeon, Denyse (Cahiers d'histoire, 1996)
issued: 1996-21-00
Keywords: Femmes; Histoire

L'homicide conjugal à Montréal de 1954 à 1962 et de 1985 à 1989 - Boisvert, Raymonde (Université de Montréal, 1996)
Keywords: Criminalité

Étude du processus de construction du sens dans les médias: le cas de la tragédie de l'École polytechnique en 1989 - Boudreau, Julie (Université de Sherbrooke, 1996)
Keywords: Devoir (Le); Femmes; Montreal Gazette; Presse (La); École polytechnique

Antiracism organizing and resistance in nursing : African Canadian Women - Calliste, Agnes (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1996)
Number: 3
Keywords: Africains; Femmes; Infirmières; Noirs

Femmes de mœurs légères au XVIIe siècle - Charbonneau, Hubert (Mémoires de la Société généalogique canadienne-française, 1996)
Lien avec Montréal – énumération de femmes bannies ou autres pour des moeurs légères. Petite analyse.
issued: 1996-22-00
Keywords: Femmes

Analyse critique d'un processus de recherche-action réalisé dans un organisme communautaire: le Centre communautaire des gais et lesbiennes de Montréal - Gagnon, Stéphanie (Université de Montréal, 1996)

Roughing It In Suburbia: Reading Chatelaine Magazine 1950-1969 - Korinek, Valerie Joyce (University of Toronto, 1996)
Keywords: Femmes; Féminisme

Criminal Women and Bad Girls: Regulation and Punishment in Montreal, 1890-1930 - Myers, Tamara (Université McGill, 1996)
Keywords: Criminalité; Délinquance; Femmes; Prisons

Women in Montreal during Three Wars: an Examination of Gender, Nationalism and Colonialism - Pickles, Katie (Université McGill, 1996)
Keywords: Femmes; Guerre; Nationalisme

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Familles ouvrières à Montréal. Âge, genre et survie quotidienne pendant la phase d’industrialisation - Bradbury, Bettina (Boréal, 1995)
Keywords: Alimentation; Famille; Logement; Vêtements

Les élues politiques et la représentation des intérêts des femmes: le cas des conseillères municipales du Rassemblement des citoyens et citoyennes de Montréal (RCM) - Diagne, Aminata (Université du Québec à Montréal, 1995)
Keywords: Femmes; Rassemblement des citoyens et citoyennes de Montréal

La solidarité entre générations: Haïtiennes âgées à Montréal - Haldemann, Varena (Sociologie et sociétés, 1995)
issued: 1995-23-00
Keywords: Femmes; Haïtiens

A Study of the Effects of Acculturation on Sex-Role Attitudes of Chinese Couples, and the Subsequent Impact of these Sex-Role Attitudes on Couple's Household Task Sharing & Decision Making - Hayes, Janet (Université Concordia, 1995)
Keywords: Chinois; Femmes

La tragédie de l'École Polytechnique: analyse sociologique des discours d'acteurs sociaux qui l'ont commentée - Lamoureux, Jean-Claude (Université de Montréal, 1995)
Keywords: Femmes; École polytechnique

La citoyenne selon Éva Circé-Côté - Lévesque, André (Résistance et transgression. Études en histoire des femmes au Québec, 1995)
Keywords: Circé-Côté; Éva; Femmes; Féminisme; Journalistes; Élections

Housing the Grey Nuns: Power, Religion and Women in fin-de-siècle Montréal - Martin, Tania Marie (Université McGill, 1995)
Keywords: Communautés religieuses; Couvents; Soeurs Grises

Couples en emploi et morphologie sociale des quartiers de Montréal, 1971-1991 - Villeneuve, Paul (Sociologie et sociétés, 1995)
issued: 1995-23-00
Keywords: Femmes; Quartiers; Travail

L'homicide conjugal à Montréal - Boisvert, Raymond; Cusson, Maurice (Recherches sociographiques, 1994)
Number: 2
Keywords: Criminalité

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
issued: 1994-21-00
Keywords: Famille; Femmes

BARRY, ROBERTINE, Françoise - Carrier, Anne (Dictionnaire biographique du Canada, 1994)

Le lesbianisme à Montréal entre 1950 et 1972: une analyse sociologique d'expériences vécues - Chamberland, Line (Université de Montréal, 1994)
Keywords: Femmes

Ces femmes qui ont bâti Montréal. La petite et la grande histoire des femmes qui ont marqué la vie de Montréal depuis 350 ans - Darsigny, Maryse; Descarries, Francine; Kurtzman, Lyne; Tardy, Évelyne (Remue-ménage, 1994)
Keywords: Femmes

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Boréal, 1994)
Keywords: Femmes; Prostitution

Femmes immigrantes et sida: les Haïtiennes de Montréal - Landry, Gervaise Patricia (Université Laval, 1994)
Keywords: Femmes; Haïtiens

La signification du travail dans les communautés religieuses féminines: 1900-1965 - Laurin, Nicole; Spielvogel, Myriam (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Communautés religieuses; Travail

Les Québécoises et leur citoyenneté. La citoyenneté selon Éva Circé-Côté - Lévesque, Andrée (La Politique des droits. Citoyenneté et construction des genres au 19e et 20e siècles, 1994)
Keywords: Circé-Côté; Éva; Femmes; Féminisme; Journalistes; Élections

Making and Breaking the Rules. Women in Quebec, 1919-1939 - Lévesque, Andrée (McClelland & Stewart, 1994)
Translators: _:n8836
Keywords: Avortement; Famille; Femmes; Prostitution

Trajectoires du féminisme contemporain, 1970-1990 - Maillé, Chantal (Le Devoir: reflet du Québec au 20e siècle, 1994)
Keywords: Femmes; Féminisme

Une place à soi? Aspects du célibat féminin laïc à Montréal à la fin du 19e siècle - Renaud, Catherine (Université de Montréal, 1994)
Keywords: Femmes

Gender and Division of Labour in a Vietnamese-Canadian Buddhist Pagoda - Soucy, Alexander (Université Concordia, 1994)
Keywords: Femmes; Travail; Vietnamiens

The Promise: Communist Organizing in the Needle Trades, the Dressmakers' Campaign, 1928-1937 - Steedman, Mercedes (Labour / Le travail, 1994)
Keywords: Communistes; Confection; Femmes; Travail

Une cité à bâtir: des femmes dans la lutte pour le changement social - Wakeling, Faye (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Femmes; Église Unie

Les infirmières de la Métropolitaine au service des Montréalaises - Baillargeon, Denyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Assurance; Femmes; Infirmières

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1993)
Keywords: Crise; Famille; Femmes

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

Le formalisme au féminin. Rita Letendre. Peintre et muraliste - Carani, Marie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Peinture

La consultation publique à Montréal: un affaire de femmes? - Cloutier, Céline (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

La sécurité des femmes dans la ville - Cousineau, Léa (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Le verre-écran de Marcelle Ferron, station de métro de Champ de Mars: la querelle des anciens et des modernes - Couture, Francine (Les Bâtisseuses de la Cité, 1993)
Keywords: Champ-de-Mars; Transport en commun; Vitraux

L’histoire des femmes dans le cinéma au Québec des débuts à 1969 - Denault, Jocelyne (Université de Montréal, 1993)
Keywords: Cinéma; Femmes

Madeleine de La Peltrie et la fondation de Montréal - Deroy-Pineau, Françoise (Les Bâtisseuses de la Cité, 1993)

Les religieuses enseignantes auraient-elles fait la Révolution tranquille si on leur en avait laissé le temps? - Hamel, Thérèse (Les Bâtisseuses de la Cité, 1993)
Keywords: Communautés religieuses; Enseignants

Le leadership féminin dans les associations privées de charité protestantes au XIXe siècle à Montréal - Harvey, Janice (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Protestants

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
Number: 51
Keywords: Droit; Famille; Femmes; Mariage; Médecine; Théologie

La communication musicale à travers des femmes que j'ai connues - Kendergi, Maryvonne (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Musique

La fin d'un univers féminin: l'Enquête Caron et la prostitution, 1945-1965 - Lacasse, Danielle (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Prostitution

L'animation de la paroisse montréalaise: un aspect méconnu du travail des femmes dans la ville. Les années 1950 - Lafortune, Agathe (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Travail

The First Generation: the Experience of Women University Students in Central Canada - LaPierre, Paula Jane Sophia (Université de Toronto, 1993)
Keywords: Femmes

Existe-t-il une musique dite féministe? - Lefebvre, Marie-Thérèse (Les Bâtisseuses de la Cité, 1993)
Keywords: Féminisme; Musique

Elles disent leur dépaysement et bâtissent leur repaysement - Lequin, Lucie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Journaliste au masculin: Éva Circé-Côté (1871-1949) - Lévesque, Andrée (Les Bâtisseuses de la Cité, 1993)
Keywords: Circé-Côté; Éva; Journalistes

La ville: un milieu d'engagement politique privilégié pour les femmes: le cas de Montréal - Maillé, Chantal (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Les congrégations féminines et la fondation des écoles normales de filles à Montréal - Malouin, Marie-Paule (Les Bâtisseuses de la Cité, 1993)
Keywords: Communautés religieuses; Écoles normales

La musique composée au féminin - Martin-Kostajnsek, Sylvaine (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Musicien; Musique

Sweated Labour: Female Needleworkers in Industrializing Canada - McIntosh, Robert (Labour / Le travail, 1993)
Keywords: Confection; Femmes; Travail

Les Québécoises et le mouvement pacifiste (1939-1967) - Monet-Chartrand, Simonne (Écosociété, 1993)
Keywords: Femmes; Guerre

Women Policing Women: A Patrol Woman in Montreal in the 1910s - Myers, Tamara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
Number: 1
Keywords: Femmes; Police

Y a-t-il une musique virile? - Panneton, Isabelle (Les Bâtisseuses de la Cité, 1993)
Keywords: Musique

L'importance des femmes dans la vie musicale montréalaise entre les deux guerres: mythe ou réalité? - Paul, Hélène (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Musicien; Musique

Les femmes et la prise de décision au niveau municipal - Pelletier, Lyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Conseillers municipaux; Femmes

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger; Jacques

Elles, dans la ville - Saint-Martin, Lori (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Marie Morin: vivante mémoire des amazones de Ville-Marie - Théry, Chantal (Les Bâtisseuses de la Cité, 1993)
Keywords: Morin; Marie

Accession des femmes à l'enseignement supérieur et origines d'une pratique architecturale féminine - Tremblay, Katia (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Les femmes "peintres de la cité" - Trépanier, Esther (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Peinture

Projets et pratiques de femmes architectes - Vescei, Éva (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Des hommes en quête d'épouse - Bates, Réal (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)
Keywords: Mariage

Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

L'histoire des femmes au Québec depuis quatre siècles - Collectif Clio (Le Jour, 1992)
Keywords: Femmes

The Montreal YWCA and Its Role in the Advancement of Women: 1920-1960 - Davies, Elaine (Université Concordia, 1992)
Keywords: Femmes; Young Women's Christian Association (YWCA)

Étude socio-pragmatique du discours publicitaire en fonction de la variable "sexe": le cas des pilules rouges et des pilules Moro (1910-1950) - Dubost, Vincent (Université du Québec à Trois-Rivières, 1992)
Keywords: Publicité

Orphelines en France, pionnières au Canada: les Filles du roi au XVIIe siècle; suivi d'un Répertoire biographique des Filles du roi - Landry, Yves (Leméac, 1992)
Keywords: Femmes; Filles du Roi

Quand les ménagères se font militantes: la Ligue auxiliaire de l'Association internationale des machinistes, 1905-1980 - Murray, Sylvie (Labour / Le travail, 1992)
Keywords: Femmes

Les femmes et le vote au Bas-Canada de 1792 à 1849 - Picard, Nathalie (Université de Montréal, 1992)
Keywords: Femmes; Élections

Entre l'accès à l'égalité et la préservation des modèles: ambivalence du discours et des revendications du Comité féminin de la CTCC-CSN, 1952-1966 - Piché, Lucie (Labour / Le travail, 1992)
issued: 1992-21-00
Keywords: Confédération des syndicats nationaux; Confédération des travailleurs catholiques du Canada (C.T.C.C.); Femmes; Féminisme; Travail

Les femmes et le logement: une situation particulière - Pilote, Ruth; Mondor, Françoise (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Femmes; Logement

Le discours médical et l'image de la féminité: les publicités pharmaceutiques dans les revues Châtelaine et Médecin du Québec (1965-1980) - Tremblay, Danielle (Université de Sherbrooke, 1992)
Keywords: Femmes; Médecine; Produits pharmaceutiques; Publicité

Struggling on Many Fronts: Gender, Work and Unionization - Aguiar, Luis (McMaster University, 1991)
Keywords: Textile; Vêtements

Maîtresses de maison dépareillées? L'apprentissage du travail domestique à Montréal au début du siècle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
issued: 1991-22-00
Keywords: Enfants; Famille; Femmes

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1991)
Keywords: Crise; Famille; Femmes

Devenir avocate: l'entrée des femmes dans une profession juridique au Québec, 1911-1985 - Bélanger, Sylvie (Université de Sherbrooke, 1991)
Keywords: Avocats; Femmes

Domaine et tours du fort des messieurs de Saint-Sulpice - Casavant, Germain (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Autochtones; Patrimoine; Sulpiciens

Jouer aux éclats: l’inscription spectaculaire des cultures de femmes dans le théâtre de Jovette Marchessault - Forsyth, Louise (Voix et Images, 1991)
Number: 2
Keywords: Femmes; Théâtre; Écrivains

Domaine des soeurs grises de Montréal - Gauthier, Raymonde (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Femmes; Patrimoine; Soeurs Grises

Amazons and Victims: Resisting Wife-Abuse in Working-Class Montréal, 1869-1879 - Harvey, Kathryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
Number: 1
Keywords: Femmes; Tempérance

To Love, Honour and Obey, Wife-Battering in Working-Class Montreal, 1869-1879 - Harvey, Kathryn (Université de Montréal, 1991)
Keywords: Famille; Femmes

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Université d'Ottawa, 1991)
Keywords: Femmes; Prostitution

Hello, Central? Gender, Technology and Culture in the Formation of Telephone Systems - Martin, Michèle (McGill-Queen's University Press, 1991)
Keywords: Bell Canada; Femmes; Téléphone

Les vocations féminines de la région montréalaise au XIXe siècle - Payette, Céline (Université du Québec à Montréal, 1991)
Keywords: Communautés religieuses; Femmes

La femme et l'avortement à la fin du XIXe siècle: les points de vue d'un médecin rigoriste et d'un médecin français jugé déviant - Potvin, Yolande (Université du Québec à Trois-Rivières, 1991)
Keywords: Avortement; Femmes; Médecine

Prostitution juvénile masculine et identité personnelle - Trottier, Germain (Université de Montréal, 1991)
Keywords: Enfants; Prostitution

To Love, Honour and Obey: Wife-Battering in Working-class Montreal, 1869-1879 - Harvey, Kathryn (Urban History Review / Revue d'histoire urbaine, 1990)
Number: 2
Keywords: Famille; Femmes

Il était une foi... 1890-1990. Scruter le présent. Façonner l'avenir. Recueil de textes à l'occasion du centenaire de Marie Gérin-Lajoie (Institut du Bon Conseil, 1990)
Keywords: Gérin-Lajoie; Marie; Institut du Bon-Conseil

Gender at Work at Home: Family Decisions, the labour Market and Girl's Contributions to the Family Economy - Bradbury, Bettina (Canadian and Australian Labour History. Toward a Comparative Perspective, 1990)
Keywords: Enfants; Famille; Femmes; Travail

Travail d'ombre et de lumière. Le bénévolat féminin à l'Hôpital Sainte-Justine 1907-1960 - Charles, Aline (Institut québécois de recherche sur la culture, 1990)
Keywords: Bénévolat; Femmes; Hôpital Sainte-Justine; Hôpitaux

L’émergence des écrits des femmes dans les Écrits du Canada français 1954-1973 - des Rivières, Marie-José (Voix et Images, 1990)
Number: 2
Keywords: Femmes; Écrivains

La syndicalisation des femmes dans l'industrie montréalaise du vêtement, 1936-1937 - Gagnon, Gemma (Université du Québec à Montréal, 1990)
Keywords: Confection; Femmes; Grèves; Union internationale des ouvriers du vêtement pour dames; Vêtements

Les femmes à l'Université de Montréal, vues à travers un journal étudiant: Le Quartier Latin, 1927-1945 - Lemaire, Christine (Université de Montréal, 1990)
Keywords: Femmes; Quartier latin (Le); Université de Montréal; Étudiants

La santé des femmes en période de dépression économique: l'exemple des patientes de l'Hôpital de la Miséricorde à Montréal pendant les années trente (notes de recherche) - Lévesque, Andrée (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1990)
issued: 1990-22-00/1990-23-00
Keywords: Crise; Femmes; Hôpital de la Miséricorde; Hôpitaux

Maternité et pathologie: étude du discours médical sur la grossesse et l'accouchement au Québec (1870-1900) - Naubert, Hélène (Université du Québec à Trois-Rivières, 1990)
Keywords: Femmes; Médecine

Women and Political Participation: the Montreal Citizens Movement, 1974-1989 - Van der Veen, Paula Louise (Université McGill, 1990)
Keywords: Femmes; Rassemblement des citoyens et citoyennes de Montréal

Itinéraires professionnels masculins et féminins en milieu bancaire: le cas de la Banque d'Hochelaga, 1900-1929 - Dagenais, Michèle (Labour / Le travail, 1989)
issued: 1989-23-00
Keywords: Banque d'Hochelaga; Banques; Femmes; Travail

La norme et les déviantes. Des femmes au Québec pendant l'entre-deux guerres - Lévesque, Andrée (Remue-Ménage, 1989)
Keywords: Femmes; Hôpital de la Miséricorde; Hôpitaux; Prostitution

Le bénévolat féminin en milieu hospitalier: le cas de l'hôpital Ste-Justine 1907-1960 - Charles, Aline (Université du Québec à Montréal, 1988)
Keywords: Bénévolat; Femmes; Hôpital Sainte-Justine; Hôpitaux

La formation professionnelle des filles au Québec: l'exemple des Business Colleges, 1930-1960 - Dompierre, Julie (Université de Sherbrooke, 1988)
Keywords: Femmes; Travail

Savoir contrôlé ou pouvoir confisqué? La formation des filles en technologie médicale, réhabilitation et diététique à l'Université de Montréal (1940-1970) - Fahmy-Eid, Nadia; Charles, Aline (Recherches féministes, 1988)
Number: 1
Keywords: Diététique; Femmes; Réhabilitation; Technologie médicale; Université de Montréal

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Quebec Women: a History - Collectif Clio (Women's Press, 1987)
Translators: _:n14097
Keywords: Femmes

Division sexuelle du travail en milieu bancaire: Montréal, 1900-1930 - Dagenais, Michèle (Université du Québec à Montréal, 1987)
Keywords: Banques; Femmes; Travail

Taking the Veil: An Alternative to Marriage, Motherhood, and Spinsterhood in Quebec, 1840-1920 - Danylewycz, Marta (McClelland and Stewart, 1987)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

La dynamique des rapports de sexes à l'université 1940-1980: une étude de cas - Collin, Johanne (Histoire sociale / Social History, 1986)
Number: 38
Keywords: Femmes; Université de Montréal

Le traitement judiciaire du viol dans le district de Montréal en 1980 face aux revendications féminines - Keller, Yves (Université de Montréal, 1986)
Keywords: Criminalité; Femmes; Tribunaux

Les communautés religieuses masculines de 1836 à 1920 - Laperrière, Guy (L'Église de Montréal, aperçus d'hier et d'aujourd'hui, 1836-1986, 1986)
Keywords: Communautés religieuses

La représentation du travail rémunéré des femmes pendant la Seconde Guerre mondiale, à travers le journal La Presse, Québec, 1939 à 1945 - Sauvé, Marie-Anne (Université du Québec à Montréal, 1986)
Keywords: Femmes; Guerre; Presse (La); Travail

Évolution des profils de comportement des clientèles féminine et masculine face aux études universitaires: le cas des facultés professionnelles de l'Université de Montréal, 1940-1980 - Collin, Johanne (Université du Québec à Montréal, 1985)
Keywords: Femmes; Université de Montréal

Changing Relationships: Nuns and Feminists in Montreal, 1890-1920 - Danylewycz, Marta (The Neglected Majority: Essays in Canadian Women's History - Volume 2, 1985)
Keywords: Collège Marguerite-Bourgeoys; Communautés religieuses; Congrégation de Notre-Dame; Femmes; Féminisme; Institut du Bon-Conseil

Marie Gérin-Lajoie. De mère en fille, la cause des femmes - Pelletier-Baillargeon, Hélène (Boréal Express, 1985)
Keywords: Femmes; Féminisme; Gérin-Lajoie; Marie; Institut du Bon-Conseil

Entre l'usine et la cuisine (Maison du Fier-Monde, 1984)
Keywords: Femmes; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Number: 33
Keywords: Famille; Femmes; Travail

Teachers, Gender, and Bureaucratizing School Systems in Nineteenth Century Montreal and Toronto - Danylewycz, Marta; Prentice, Alison Leeds (History of Education Quarterly, 1984)
issued: 1984-21-00
Keywords: Enseignants; Femmes

Analyse sociolinguistique de deux discours féministes - Helme, Mireille (Université McGill, 1984)
Keywords: Féminisme; Les Têtes de Pioche (journal)

Françoise (Robertine Barry), pionnière du journalisme féminin au Canada - Lévesque, Gilbert (Montréal: activités, habitants, quartiers, 1984)
Keywords: Barry; Robertine; Femmes; Journalistes

From Time to Time in the Queen's Name: The Story of the Honourable Cairine Reay Mackay Wilson, Canada's First Woman Senator - Way, Agnes Rosanne (Université Carleton, 1984)
Keywords: Femmes; Wilson; Cairine

The Neglected Majority: The Changing Role of Women in Nineteen Century Montreal - Cross, D. Suzanne (The Social Development of Canada - Readings, 1983)
Keywords: Femmes

Sexes et classes sociales dans l'enseignement: le cas de Montréal à la fin du 19e siècle - Danylewycz, Marta (Maîtresses de maison, maîtresses d'école, 1983)
Keywords: Enseignants; Femmes

The Evolution of the Sexual Division of Labour in Teaching: A Nineteenth-Century Ontario and Quebec Case Study - Danylewycz, Marta (Histoire sociale / Social History, 1983)
Number: 31
Keywords: Enseignants; Femmes; Travail

Les débuts du mouvement des femmes à Montréal, 1893-1902 - Pinard, Yolande (Travailleuses et féministes. Les femmes dans la société québécoise, 1983)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme; Montreal Local Council of Women

La genèse et l'évolution du mouvement de libération des femmes à Montréal, 1969-79 - Lanctot, Martine (Université du Québec à Montréal, 1982)
Keywords: Femmes; Féminisme

Changing Relationships: Nuns and Feminists in Montreal, 1890-1925 - Danylewycz, Marta (Histoire sociale / Social History, 1981)
Number: 28
Keywords: Collège Marguerite-Bourgeoys; Communautés religieuses; Congrégation de Notre-Dame; Femmes; Féminisme; Institut du Bon-Conseil

Thérèse Casgrain - Bertrand, Réal (Lidec, 1981)
Keywords: Femmes; Féminisme; Élections

Taking the Veil in Montreal, 1840-1920: An Alternative to Marriage, Motherhood and Spinsterhood - Danylewycz, Marta (Université de Toronto, 1981)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Premières brèches dans l'idéologie des deux sphères: Joséphine Marchand-Dandurand et Robertine Barry, deux journalistes montréalaises de la fin du XIXe siècle - Thibeault, Diane (Université d'Ottawa, 1981)
Keywords: Barry; Robertine; Femmes; Féminisme; Journalistes; Marchand-Dandurand; Joséphine

The Montreal Section of the National Council of Jewish Women: The Paradox of Being a Mother - Forman, Debra (Université Concordia, 1980)
Keywords: Femmes; Féminisme; Juifs; National Council of Jewish Women

Sex, Politics and Religion: Controversies in Female Immigration Reform Work in Montreal, 1881-1919 - Roberts, Barbara Ann (Atlantis, 1980)
issued: 1980-23-00
Keywords: Femmes; Protestants

A Not Unreasonable Claim. Women and Reform in Canada 1880s - 1920s - Kealey, Linda (Women's Educational Press, 1979)
Keywords: Femmes; Féminisme; Réformistes

The Fédération Nationale St-Jean-Baptiste and the Women's Movement in Quebec - Lavigne, Marie; Pinard, Yolande; Stoddart, Jennifer (A Not Unreasonable Claim. Women and Reform in Canada 1880s-1920s, 1979)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme

Françoise et Madeleine, pionnières du journalisme féminin au Québec - Boivin, Aurélien; Landry, Kenneth (Voix et Images, 1978)
Number: 2
Keywords: Femmes; Journalistes

Les orientations des femmes à l'Université de Montréal en 1949-50 et en 1974-75 - Leduc, Constance (Canadian and International Education, 1978)
Keywords: Femmes; Université de Montréal; Étudiants

La majorité oubliée: le rôle des femmes à Montréal au 19e siècle - Cross, D. Suzanne (Les femmes dans la société québécoise, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Canadian City. Essays in Urban History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Neglected Majority: Essays in Canadian Women's History, 1977)
Keywords: Femmes

La Fédération nationale Saint-Jean Baptiste et les revendications féministes au début du siècle - Lavigne, Marie; Pinard, Yolande; Stoddart, Jennifer (Les femmes dans la société québécoise, 1977)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme

Les débuts du mouvement des femmes - Pinard, Yolande (Les femmes dans la société québécoise, 1977)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme; Montreal Local Council of Women

Étude comparative des orientations universitaires des femmes à l'Université de Montréal en 1949-50 et 1974-75 - Leduc, Constance (Université de Montréal, 1976)
Keywords: Femmes; Université de Montréal; Étudiants

Des archives de femmes pour le début du siècle - Pinard, Yolande (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1976)
issued: 1976-06/1976-07
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Montreal Local Council of Women

Le féminisme à Montréal au commencement du XXe siècle (1893-1920) - Pinard, Yolande (Université du Québec à Montréal, 1976)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme; Lacoste; Marie; Montreal Local Council of Women

La crise de 1922 dans la lutte pour le suffrage féminin au Québec - Trifiro, Luigi (Université de Sherbrooke, 1976)
Keywords: Crise; Femmes

La Fédération nationale Saint-Jean-Baptiste et les revendications féministes au début du 20e siècle - Lavigne, Marie; Pinard, Yolande; Stoddart, Jennifer (Revue d'histoire de l'Amérique française, 1975)
Number: 3
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste; Féminisme

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (Histoire sociale / Social History, 1973)
Number: 12
Keywords: Femmes

Attitudes et comportements sexuels masculins et féminins: contribution empirique à l'étude comparative des sexes - Crépault, Claude (Université de Montréal, 1973)

The Development of Higher Education for Women at McGill University from 1857 to 1899 with Special Reference to the Role of Sir John William Dawson - Ronish, Donna Ann (Université McGill, 1972)
Keywords: Dawson; William; Femmes; Université McGill

The Story of Women Associates of McGill - Maas, C. E. (L'Association, 1968)
Keywords: Femmes; Université McGill

Effets du travail de la femme mariée sur la structure d'autorité: une étude du travail de la femme mariée en emploi rémunéré, au point de vue de ses conséquences sur la structure d'autorité dans la famille à partir de deux groupes d'échantillonnage comparés à Montréal, en 1963 - Laferrière, Guy; Maheu, Pierre (Université de Montréal, 1963)
Keywords: Famille; Femmes; Mariage; Travail